Актуальні питання державотворення та захисту прав людини в Україні. Вип. 5 - Хмельницький інститут ПрАТ «ВНЗ «МАУП» (My University, 2017)
У збірнику наукових праць вміщено статті з тематики «Актуальні питання державотворення і захисту прав людини в Україні». Авторами статей розкрито такі питання: конституційні права та свободи людини та громадянина; система захисту праві і свобод людини; шляхи вдосконалення законодавства України та проблеми його адаптації до правової системи Євросоюзу. The collection of scientific works contains articles on the topic "Current issues of state formation and protection of human rights in Ukraine". The authors of the articles have revealed the following issues: constitutional rights and freedoms of man and citizen; the system of protection of human rights and freedoms; ways to improve the legislation of Ukraine and the problems of its adaptation to the legal system of the European Union.